Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To determine which of the given points satisfy the system of inequalities, we need to check each point against the inequalities:
[tex]\[ \begin{array}{l} y \leq -2x + 6 \\ x > 1 \end{array} \][/tex]
Let's go through each point one by one:
### Point A: [tex]\((1, 4)\)[/tex]
1. Check [tex]\(x > 1\)[/tex]:
- [tex]\(x = 1\)[/tex]; since [tex]\(1 \leq 1\)[/tex], this point does not satisfy the inequality [tex]\(x > 1\)[/tex].
Since it fails the second inequality, point A does not satisfy the system of inequalities.
### Point B: [tex]\((2, 1)\)[/tex]
1. Check [tex]\(x > 1\)[/tex]:
- [tex]\(x = 2\)[/tex]; since [tex]\(2 > 1\)[/tex], this point satisfies the inequality [tex]\(x > 1\)[/tex].
2. Check [tex]\(y \leq -2x + 6\)[/tex]:
- Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 1\)[/tex]: [tex]\(1 \leq -2(2) + 6\)[/tex] which simplifies to [tex]\(1 \leq 2\)[/tex].
Since it satisfies both inequalities, point B does satisfy the system of inequalities.
### Point C: [tex]\((0, 6)\)[/tex]
1. Check [tex]\(x > 1\)[/tex]:
- [tex]\(x = 0\)[/tex]; since [tex]\(0 \leq 1\)[/tex], this point does not satisfy the inequality [tex]\(x > 1\)[/tex].
Since it fails the second inequality, point C does not satisfy the system of inequalities.
### Point D: [tex]\((2, 11)\)[/tex]
1. Check [tex]\(x > 1\)[/tex]:
- [tex]\(x = 2\)[/tex]; since [tex]\(2 > 1\)[/tex], this point satisfies the inequality [tex]\(x > 1\)[/tex].
2. Check [tex]\(y \leq -2x + 6\)[/tex]:
- Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 11\)[/tex]: [tex]\(11 \leq -2(2) + 6\)[/tex] which simplifies to [tex]\(11 \leq 2\)[/tex].
Since it fails the first inequality, point D does not satisfy the system of inequalities.
### Point E: [tex]\((5, -6)\)[/tex]
1. Check [tex]\(x > 1\)[/tex]:
- [tex]\(x = 5\)[/tex]; since [tex]\(5 > 1\)[/tex], this point satisfies the inequality [tex]\(x > 1\)[/tex].
2. Check [tex]\(y \leq -2x + 6\)[/tex]:
- Substitute [tex]\(x = 5\)[/tex] and [tex]\(y = -6\)[/tex]: [tex]\(-6 \leq -2(5) + 6\)[/tex] which simplifies to [tex]\(-6 \leq -4\)[/tex].
Since it satisfies both inequalities, point E does satisfy the system of inequalities.
### Conclusion
The points that satisfy the system of inequalities are:
- B. [tex]\((2, 1)\)[/tex]
- E. [tex]\((5, -6)\)[/tex]
Thus, the solutions to the system of inequalities are:
[tex]\[ \{(2, 1), (5, -6)\} \][/tex]
[tex]\[ \begin{array}{l} y \leq -2x + 6 \\ x > 1 \end{array} \][/tex]
Let's go through each point one by one:
### Point A: [tex]\((1, 4)\)[/tex]
1. Check [tex]\(x > 1\)[/tex]:
- [tex]\(x = 1\)[/tex]; since [tex]\(1 \leq 1\)[/tex], this point does not satisfy the inequality [tex]\(x > 1\)[/tex].
Since it fails the second inequality, point A does not satisfy the system of inequalities.
### Point B: [tex]\((2, 1)\)[/tex]
1. Check [tex]\(x > 1\)[/tex]:
- [tex]\(x = 2\)[/tex]; since [tex]\(2 > 1\)[/tex], this point satisfies the inequality [tex]\(x > 1\)[/tex].
2. Check [tex]\(y \leq -2x + 6\)[/tex]:
- Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 1\)[/tex]: [tex]\(1 \leq -2(2) + 6\)[/tex] which simplifies to [tex]\(1 \leq 2\)[/tex].
Since it satisfies both inequalities, point B does satisfy the system of inequalities.
### Point C: [tex]\((0, 6)\)[/tex]
1. Check [tex]\(x > 1\)[/tex]:
- [tex]\(x = 0\)[/tex]; since [tex]\(0 \leq 1\)[/tex], this point does not satisfy the inequality [tex]\(x > 1\)[/tex].
Since it fails the second inequality, point C does not satisfy the system of inequalities.
### Point D: [tex]\((2, 11)\)[/tex]
1. Check [tex]\(x > 1\)[/tex]:
- [tex]\(x = 2\)[/tex]; since [tex]\(2 > 1\)[/tex], this point satisfies the inequality [tex]\(x > 1\)[/tex].
2. Check [tex]\(y \leq -2x + 6\)[/tex]:
- Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 11\)[/tex]: [tex]\(11 \leq -2(2) + 6\)[/tex] which simplifies to [tex]\(11 \leq 2\)[/tex].
Since it fails the first inequality, point D does not satisfy the system of inequalities.
### Point E: [tex]\((5, -6)\)[/tex]
1. Check [tex]\(x > 1\)[/tex]:
- [tex]\(x = 5\)[/tex]; since [tex]\(5 > 1\)[/tex], this point satisfies the inequality [tex]\(x > 1\)[/tex].
2. Check [tex]\(y \leq -2x + 6\)[/tex]:
- Substitute [tex]\(x = 5\)[/tex] and [tex]\(y = -6\)[/tex]: [tex]\(-6 \leq -2(5) + 6\)[/tex] which simplifies to [tex]\(-6 \leq -4\)[/tex].
Since it satisfies both inequalities, point E does satisfy the system of inequalities.
### Conclusion
The points that satisfy the system of inequalities are:
- B. [tex]\((2, 1)\)[/tex]
- E. [tex]\((5, -6)\)[/tex]
Thus, the solutions to the system of inequalities are:
[tex]\[ \{(2, 1), (5, -6)\} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.